Revise : the scholar-writer's essential guide to tweaking, editing, and perfecting your manuscript - Haag, Pamela (Yale University Press, 2021)
"A helpful, engaging guide to the revision of scholarly writing by an editor and award-winning author "Pamela Haag has been called 'the tenure whisperer' for good reason. Any scholar who hopes to attract a wider audience of readers will benefit from the brilliant, step-by-step guidance shared here. It's pure gold for all aspiring nonfiction writers."--Nancy MacLean, author of Democracy in Chains: The Deep History of the Radical Right's Stealth Plan for America Writing and revision are two different skills. Many scholar-writers have learned something about how to write, but fewer know how to read and revise their own writing, spot editorial issues, and transform a draft from passable to great. Drawing on before and after examples from more than a decade as a developmental editor of scholarly works, Pamela Haag tackles the most common challenges of scholarly writing. This book is packed with practical, user-friendly advice and is written with warmth, humor, sympathy, and flair. With an inspiring passion for natural language, Haag demonstrates how to reconcile clarity with intellectual complexity. Designed to be an in-the-trenches desktop reference, this indispensable resource can help scholars develop a productive self-editing habit, advise their graduate and other students on style, and, ultimately, get their work published and praised." --